Public and private sectors in health : economic issues. - Newbrander, William (1992)
Suggests an agenda for action by governments and international agencies to facilitate assessment of public and private roles in health. Presents a framework of public/private mix arrangements, discusses the experiences and issues of public/private mix in developing countries, and outlines a range of actions at the country level.